Choosing a Licensed Wood-Destroying Organism (WDO) Inspector - Faith M. Oi; Paul Mitola; Kathleen Ruppert (EDIS)
During 2004, there were over 100 known illegal Termite and Wood-Destroying Organism (WDO) inspectors at work in the state, filling out Form 13645. Form 13645 is important to consumers in Florida because if an inspection for termites and other WDOs is done as part of a real estate transaction, then Form 13645 is required by Florida Statute 482.266. For more information on Form 13645, as it pertains to home buyers, see http://www.flaes.org/aes-ent/termitehelp/index.html and click on Understanding Real Estate WDO report Information. In addition, the home inspection industry remains unregulated. This document is ENY-2005 (IN629), one of a series of the Department of Entomology and Nematology, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Date first published: July 2005.